2013
DOI: 10.3892/mmr.2013.1353
|View full text |Cite
|
Sign up to set email alerts
|

Bigelovii A induces apoptosis of HL-60 human acute promyelocytic leukaemia cells

Abstract: In the present study, the antitumor effects of the nor‑Oleanane type triterpene saponin, Bigelovii A, isolated from Salicornia bigelovii Torr, were examined. Bigelovii A was demonstrated to inhibit HL‑60 human acute promyelocytic leukaemia cell growth with an IC50 value of 2.15 µg/ml. In addition, Bigelovii A promoted apoptosis in HL‑60 cells, as shown by apoptotic morphological changes and the hypodiploid cell assay. Apoptotic induction by Bigelovii A was associated with the downregulation of Bcl‑2, the upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Our previous studies have shown the chemical structure of a new nor-Oleanane type triterpene saponin (Bigelovii A) isolated from the dried herbs of Salicornia bigelovii Torr. [ 17 ], and its antitumor activity has been observed in HL-60, MCF-7, and HepG2 cells [ 18 ]. However, the anti-inflammatory activity of Bigelovii A has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown the chemical structure of a new nor-Oleanane type triterpene saponin (Bigelovii A) isolated from the dried herbs of Salicornia bigelovii Torr. [ 17 ], and its antitumor activity has been observed in HL-60, MCF-7, and HepG2 cells [ 18 ]. However, the anti-inflammatory activity of Bigelovii A has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Total cell protein extract and Western blotting analysis were conducted according to the previous literature [ 9 ] (Guan et al , 2013). Primary antibodies used in this study were Bcl-2, Bax, cleaved caspase-3, cleaved caspase-7, cleaved caspase-8, cleaved caspase-9, cleaved PARP and β-actin.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, four new noroleanane-type triterpene saponins (bigelovii A, bigelovii B, Salbige A and Salbige B) were identified from S. bigelovii and S. herbacea , and three of them (bigelovii A, Salbige A and Salbige B) exhibited potential antiproliferative activity toward promyelocytic leukemia cancer cells HL-60, human breast cancer cells MCF-7, human liver cancer cells HepG2 and lung cancer cells A549 [ 6 , 8 ]. Additionally, bigelovii A regulated apoptosis of HL-60 cells by the decrease of Bcl-2 and the increase of cleaved caspase-3 [ 9 ]. However, its bioactive components in terms of their role in its antiproliferative activities and molecular mechanism have not been entirely conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al ( 9 ) reported that Bigelovii A could also mitigate LPS-induced acute lung injury by suppressing NF-κB and CCAAT/enhancer-binding protein δ pathways. Our previous studies indicated that Bigelovii A exhibited potential cytotoxicity against HL-60, MCF7, HepG2, A549, Lovo and LN229 cells ( 8 , 10 , 11 ). In particular in HL-60 cells, Bigelovii A decreased the expression of apoptosis regulator Bcl-2 (Bcl-2), activated caspase-3 and induced cell apoptosis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies indicated that Bigelovii A exhibited potential cytotoxicity against HL-60, MCF7, HepG2, A549, Lovo and LN229 cells ( 8 , 10 , 11 ). In particular in HL-60 cells, Bigelovii A decreased the expression of apoptosis regulator Bcl-2 (Bcl-2), activated caspase-3 and induced cell apoptosis ( 10 ). However, the anti-tumor mechanism of Bigelovii A in human breast cancer cells has not been examined.…”
Section: Introductionmentioning
confidence: 99%